If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 3 = 18 Reorder the terms: 3 + 25x = 18 Solving 3 + 25x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 25x = 18 + -3 Combine like terms: 3 + -3 = 0 0 + 25x = 18 + -3 25x = 18 + -3 Combine like terms: 18 + -3 = 15 25x = 15 Divide each side by '25'. x = 0.6 Simplifying x = 0.6
| 5.5=6.7-0.4x | | 2.2x-0.2y=1.2 | | (5x-4)(7x+2)=0 | | 62=4x-2 | | -17-4= | | 13/56+5/7= | | 1.5-2x=7.5 | | 60=4x-2 | | 24x+21=36x-8 | | 6(2x-2)=-36 | | 5-(2-(-4)-6)= | | 2y-8=y+13 | | 4x-x=36 | | 7x=51 | | Y=20x+-37 | | 2(5x+3)=27 | | 8-((-4)-5)= | | (8x)(-4x)(-3x)= | | 5(x+1)+3=-17 | | 25x^2=-100 | | 2*x^2+9x=5 | | 2x^3-75x+150=0 | | 8-23= | | -x^2+19x+66=0 | | 5x-1+4x^2=0 | | -2a=4a-16 | | 5(2x-5)=-15 | | 3x+2a=7a-5x | | 56=14-6d | | 4(x-3)+3x=-26 | | -2(j+9)=15 | | 3(-1+2x)=23 |